Quality of Care: View of Patient Satisfaction with Physiotherapy in Government and Private Settings in Dhaka, Bangladesh - Hossain, Sheikh Jamal; Ferdousi, Jannatul; Biswas, Manaj Kumar; Mahfuz, Nageeb; Biswas, Gonopati (Faridpur Medical College Journal, 2013)
Patients' satisfaction plays an important role to attract patients for health services. It has not been closely monitored in physiotherapy; limited studies exist in this area of allied health services. The objective of the study was to determine the level of satisfaction of patients at the government and private hospitals in Dhaka and to compare between two facilities. This descriptive type of cross-sectional study was carried out with patients who sought physiotherapy care at the outdoor of Physical Medicine Department of the Dhaka Medical College Hospital (DMCH) and the Centre for Rehabilitation of Paralyzed (CRP), Mirpur, Dhaka. In total, 150 patients - 75 from each setting were interviewed. Appropriate research instruments comprising a structured and semi-structured questionnaire developed by the American Physical Therapy Association (APTA) were administered by interviewers to collect data. To find out any association among the socio-demographic characteristics, chi-squire test was applied, and the level of satisfaction was measured in percentages to compare between the two settings (government and private). Patients attendance differ because different socio-demographic characteristics and location of physical health problem in two hospital. Location of the hospital, privacy of patients, behaviour of staff members, physical qualities of hospitals (cleanliness, light, ventilation, etc.) had more than 10% variation in the level of satisfaction between the two settings. So, patient satisfaction with physiotherapy is higher in private setting than that in government setting in Dhaka. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13502 Faridpur Med. Coll. J. 2012;7(2):71-74